Perpetual Suspects A Critical Race Theory of Black and Mixed-Race Experiences of Policing - Long, Lisa J. (Palgrave Studies in Race, Ethnicity, Indigeneity and Criminal Justice, 2018)
Grounded in Critical Race Theory (CRT), this book examines black and mixed-race men and women's experiences of policing in the UK. Through an intersectional analysis of race, class and gender it analyses the construction of the suspect, illuminating the ways in which race and racism(s) shape police contact. This counter-story to the dominant narrative challenges the erasure of race through the contemporary 'diversity' agenda. Overall, this book proposes that making racism visible can disrupt power structures and make change possible. It makes a timely contribution to this significantly under-researched area and will be of interest to students, educators and scholars of Criminology, Social Sciences, Law and Humanities. It will also be of interest to criminal justice practitioners, communities and activists.